Comparison of Safety, Efficacy and Outcomes of Robot Assisted Laparoscopic Pyeloplasty vs Conventional Laparoscopy - Mantica G; Ambrosini F; Parodi S; Tappero S; Terrone C (Research and Reports in Urology, 2020)
Guglielmo Mantica, Francesca Ambrosini, Stefano Parodi, Stefano Tappero, Carlo Terrone Department of Urology, Policlinico San Martino Hospital, University of Genova, Genova, ItalyCorrespondence: Guglielmo ManticaDepartment of Urology, Policlinico San Martino Hospital, University of Genova, Largo Rosanna Benzi 10, Genova 16132, ItalyTel +39 0105553935Email guglielmo.mantica@gmail.comAbstract: Pyeloplasty is considered the gold standard for the management of ureteropelvic junction obstruction in cases of flank pain, recurrent stone formation or infection, and deteriorating renal function. Over the last two decades, minimally invasive techniques such as robotic (RALP) and laparoscopic pyeloplasty (LP) have become increasingly popular and have been moderately replacing the open approach. This paper aims to provide a comprehensive up-to-date review on safety, efficacy and outcomes regarding robotic repair of UPJO compared to the conventional laparoscopic procedure. RALP represents a viable and innovative alternative to conventional LP with a comparable success and complication rate both in adult and in paediatric fields. The robotic approach seems to add further technical advantages when compared to conventional LP but sustains a higher costs. Currently, the choice to adopt one of the different minimally invasive approaches depends on the surgeon’s preference or experience, and on institutional availability.Keywords: robotic pyeloplasty, laparoscopic pyeloplasty, ureteropelvic junction obstruction, hydronephrosis, pyeloplasty